HUBUNGAN ANTARA FREKUENSI KEHAMILAN DENGAN HIPERTENSI DI PUSKESMAS SUKAWALI KABUPATEN TANGERANG-BANTEN TAHUN 2021 - Siti Saropah; Nuryanih Nuryanih; Febi ratnasari (Nusantara Hasana Journal, 2022)
Hypertension in pregnancy is strongly influenced by many factors other than the characteristic factor itself, an important role in the occurrence of hypertension in pregnancy is immunological factors. starting from the last 4 months of January-April 2021, there were 372 pregnant women and 90 pregnant women. The purpose of the study was to determine the relationship between pregnancy frequency and pregnancy hypertension at the Sukawali Public Health Center, Tangerang-Banten Regency. Research design: The method in this study is quantitative with a descriptive approach to population correlation used in this study pregnant women at Puskesmas Sukawali, Kec. Pakuhaji 78 respondents. This sampling technique uses a random sampling technique. The results of the study showed that pregnant women with gestational hypertension were 15 respondents (19.2), of which 63 respondents were pre-eclamptic hypertension (80.8). At 2 years gestation, none of them had gestational hypertension. At a distance of 2-5 years of pregnancy there are 15 respondents with 19.2%, and at a distance of 2 years of pregnancy there are 63 respondents who experience preeclampsia with hypertension with 80.8%. value 0.05, which is 0.000, means that the majority of respondents with preeclampsia hypertension are more than gestational hypertension. The conclusions and suggestions in this study are that there is a relationship between the frequency of pregnancy and hypertension. Pregnant women are expected to always make visits to the puskesmas to check their pregnancy, and pregnant women are advised to follow the existing programs at the puskesmas in order to increase behavioral changes and awareness of pregnant women about the importance of health during pregnancy.